Influence of temperature variability on physiological, hematological and biochemical profiles of growing and adult Karan Fries cattle - BHAN, CHANDRA; SINGH, S V; HOODA, O K; UPADHYAY, R C; BEENAM, BEENAM (The Indian Journal of Animal Sciences, 2013)
Temperature variability impact on physiological, hematological and biochemical parameters of growing and adult Karan Fries cattle was studied during hot humid, winter, spring and summer. During forenoon and afternoon the respiration rate (RR) and rectal temperature (RT) increased by 4.67 and 3.67 breaths/min and 0.87°C and 0.77°C respectively in growing KF cows during summer over spring. The respective values increased in adult KF cows to 2.83 and 6.67 breaths/min and 0.79°C and 0.88°C during forenoon and afternoon during summer over spring. Similar pattern of increase in skin temperature (ST) and pulse rate (PR) was observed during summer and hot humid season over the spring season. The hematological parameters, viz. packed cell volume (PCV) and hemoglobin (Hb) were significantly higher during summer compared to other seasons of the year in both groups of animals. The hematological parameters (RBC, WBC, Hb and PCV) were lower during afternoon compared to forenoon in both groups of cattle during different seasons. The plasma enzymes (ALT, AST, ALP, LDH) activity were significantly higher (P